Strategi UMKM Dalam Meningkatkan Penjualan Berdasar Perspektif Syariah - Wiwin Suhada; Mohammad Sigit Adi Nugraha; Triana Apriani; Frilla Gunariah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research is motivated by the concept of sharia marketing which currently continues to develop along with the development of the sharia economy. Currently, many MSMEs are competing in the market. To survive and be competitive, good management is needed, marketing is one of them. The aim of this research is to find out MSME Strategy for Increasing Sales Based on a Sharia Perspective. The research method used is a descriptive qualitative research method. Research results show that marketing MSMEs implement sharia, namely, MSMEs always apply Islamic values ​​in their products both in terms of halal products and materials and tools, carry out their marketing activities always referring to flexibility, highly uphold mutual respect so that anyone who comes or buys the product will served as best as possible regardless of race or whatever, providing service as usual such as treating consumers well, maintaining communication with consumers, behaving in a friendly and polite manner.